2000
DOI: 10.1016/s0022-5347(05)67494-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neurokinin Receptors in the Behavioral Effect of Intravesical Antigen Infusion in Guinea Pig Bladder

Abstract: These results suggest a role for activation of NK1 and NK2, but not NK3 receptors, by tachykinins released from capsaicin-sensitive nerves, in the increased abdominal licking behavior response of guinea pigs to intravesical antigen infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…In brief, the finding that NK 3 receptor antagonism inhibited pelvic afferent nerve firing in response to CRD, but not to urinary bladder distension, indicated a locus of action within the intestine itself. This suggestion is consistent with the inability of SB‐235375 to reduce guinea‐pigs’ nociceptive behaviour induced via the urinary bladder by intravesical antigen infusion 33 . Thus, one proposal was that the efficacy of NK 3 receptor antagonism might depend on an ability to inhibit at least one function of the intrinsic primary afferent neurones (IPANs) within the enteric nervous system.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In brief, the finding that NK 3 receptor antagonism inhibited pelvic afferent nerve firing in response to CRD, but not to urinary bladder distension, indicated a locus of action within the intestine itself. This suggestion is consistent with the inability of SB‐235375 to reduce guinea‐pigs’ nociceptive behaviour induced via the urinary bladder by intravesical antigen infusion 33 . Thus, one proposal was that the efficacy of NK 3 receptor antagonism might depend on an ability to inhibit at least one function of the intrinsic primary afferent neurones (IPANs) within the enteric nervous system.…”
Section: Discussionsupporting
confidence: 63%
“…This suggestion is consistent with the inability of SB-235375 to reduce guinea-pigs' nociceptive behaviour induced via the urinary bladder by intravesical antigen infusion. 33 Thus, one proposal was that the efficacy of NK 3 receptor antagonism might depend on an ability to inhibit at least one function of the intrinsic primary afferent neurones (IPANs) within the enteric nervous system. This hypothesis suggests that when IPANs are stimulated at relatively intense levels (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The present work indicates that SB‐235375 (20 mg kg −1 ) is selective for the inhibition of responses to noxious distension of the gut, without affecting responses to noxious somatic stimuli and with comparatively small effects on intestinal motility. It has been previously reported that SB‐235375 has little effect on the pain of urinary bladder distension or inflammation 9, 24 . We determined that i.v.…”
Section: Discussionmentioning
confidence: 96%
“…For example, the behavioral response to noxious stimulation of the bladder is greatly decreased in mice and guinea pigs treated with NK‐1 antagonists (Laird et al. 2000; Ruggieri et al. 2000).…”
Section: Introductionmentioning
confidence: 99%